Revealing the interference effect of Majorana fermions in a topological Josephson junction - Liu, Jie; Yu, Tiantian; Song, Juntao (Beilstein Journal of Nanotechnology, 2018)
We study theoretically the local density of states (DOS) in a topological Josephson junction. We show that the well-known 4π Josephson effect originates from the interference effect between two Majorana fermions (MFs) that are localized at the Josephson junction. In addition, the DOS for electrons (holes) shows the 4π interference information along each parity conserved energy spectrum. The DOS displays a 2π period oscillation when two trivial states interfere with each other. This means that the DOS information may be used to distinguish the MFs from trivial localized states. We suggest that the interference effect and the DOS can be detected by using two STM leads or two normal leads. A single side lead can only detect the Andreev reflection tunneling process in the junction, which cannot reveal information about the interference effect in general. However, using two side leads, we can reveal information about the interference effect of the MFs as well as the DOS by combining Andreev reflection with the electron transmission process.
Keywords: density of states; fractional Josephson effect; Majorana fermion

(untitled) - Kitaev, A. Yu. (Phys.-Usp., 2001)

(untitled) - Nayak, C.; Simon, S. H.; Stern, A.; Freedman, M.; Das Sarma, S. (Rev. Mod. Phys., 2008)

(untitled) - Fujimoto, S. (Phys. Rev. B, 2008)

(untitled) - Sau, J. D.; Lutchyn, R. M.; Tewari, S.; Das Sarma, S. (Phys. Rev. Lett., 2010)

(untitled) - Sato, M.; Takahashi, Y.; Fujimoto, S. (Phys. Rev. B, 2010)

(untitled) - Alicea, J. (Phys. Rev. B, 2010)

(untitled) - Lutchyn, R. M.; Sau, J. D.; Das Sarma, S. (Phys. Rev. Lett., 2010)

(untitled) - Oreg, Y.; Refael, G.; von Oppen, F. (Phys. Rev. Lett., 2010)

(untitled) - Potter, A. C.; Lee, P. A. (Phys. Rev. B, 2011)

(untitled) - Nadj-Perge, S.; Drozdov, I. K.; Bernevig, B. A.; Yazdani, A. (Phys. Rev. B, 2013)

(untitled) - Klinovaja, J.; Stano, P.; Yazdani, A.; Loss, D. (Phys. Rev. Lett., 2013)

(untitled) - Mourik, V.; Zuo, K.; Frolov, S. M.; Plissard, S. R.; Bakkers, E. P. A. M.; Kouwenhoven, L. P. (Science, 2012)

(untitled) - Deng, M. T.; Yu, C. L.; Huang, G. Y.; Larsson, M.; Caroff, P.; Xu, H. Q. (Nano Lett., 2012)

(untitled) - Das, A.; Ronen, Y.; Most, Y.; Oreg, Y.; Heiblum, M.; Shtrikman, H. (Nat. Phys., 2012)

(untitled) - Nadj-Perge, S.; Drozdov, I. K.; Li, J.; Chen, H.; Jeon, S.; Seo, J.; MacDonald, A. H.; Bernevig, B. A.; Yazdani, A. (Science, 2014)

(untitled) - Law, K. T.; Lee, P. A.; Ng, T. K. (Phys. Rev. Lett., 2009)

(untitled) - Wimmer, M.; Akhmerov, A. R.; Dahlhaus, J. P.; Beenakker, C. W. J. (New J. Phys., 2011)

(untitled) - Liu, J.; Potter, A. C.; Law, K. T.; Lee, P. A. (Phys. Rev. Lett., 2012)

(untitled) - Bagrets, D.; Altland, A. (Phys. Rev. Lett., 2012)

(untitled) - Zhang, H.; Gül, Ö.; Conesa-Boj, S.; Nowak, M. P.; Wimmer, M.; Zuo, K.; Mourik, V.; de Vries, F. K.; van Veen, J.; de Moor, M. W. A.; Bommer, J. D. S.; van Woerkom, D. J.; et al. (Nat. Commun., 2017)

(untitled) - Albrecht, S. M.; Higginbotham, A. P.; Madsen, M.; Kuemmeth, F.; Jespersen, T. S.; Nygård, J.; Krogstrup, P.; Marcus, C. M. (Nature, 2016)

(untitled) - Deng, M. T.; Vaitiekėnas, S.; Hansen, E. B.; Danon, J.; Leijnse, M.; Flensberg, K.; Nygård, J.; Krogstrup, P.; Marcus, C. M. (Science, 2016)

(untitled) - van Woerkom, D. J.; Proutski, A.; van Heck, B.; Bouman, D.; Väyrynen, J. I.; Glazman, L. I.; Krogstrup, P.; Nygård, J.; Kouwenhoven, L. P.; Geresdi, A. (Nat. Phys., 2017)

(untitled) - Zuo, K.; Mourik, V.; Szombati, D. B.; Nijholt, B.; van Woerkom, D. J.; Geresdi, A.; Chen, J.; Ostroukh, V. P.; Akhmerov, A. R.; Plissard, S. R.; Car, D.; Bakkers, E. P. A. M.; et al. (arXiv, 2017)

(untitled) - Goffman, M. F.; Urbina, C.; Pothier, H.; Nygård, J.; Marcus, C. M.; Krogstrup, P. (New J. Phys., 2017)

(untitled) - Albrecht, S. M.; Hansen, E. B.; Higginbotham, A. P.; Kuemmeth, F.; Jespersen, T. S.; Nygård, J.; Krogstrup, P.; Danon, J.; Flensberg, K.; Marcus, C. M. (Phys. Rev. Lett., 2017)

(untitled) - Feldman, B. E.; Randeria, M. T.; Li, J.; Jeon, S.; Xie, Y.; Wang, Z.; Drozdov, I. K.; Andrei Bernevig, B.; Yazdani, A. (Nat. Phys., 2017)

(untitled) - Zhang, H.; Liu, C.-X.; Gazibegovic, S.; Xu, D.; Logan, J. A.; Wang, G.; van Loo, N.; Bommer, J. D. S.; de Moor, M. W. A.; Car, D.; het Veld, R. L. M. O.; van Veldhoven, P. J.; et al. (arXiv, 2017)

(untitled) - Law, K. T.; Lee, P. A. (Phys. Rev. B, 2011)

(untitled) - San-Jose, P.; Prada, E.; Aguado, R. (Phys. Rev. Lett., 2012)

(untitled) - Domínguez, F.; Hassler, F.; Platero, G. (Phys. Rev. B, 2012)

(untitled) - Crépin, F.; Trauzettel, B. (Phys. Rev. Lett., 2014)

(untitled) - Houzet, M.; Meyer, J. S.; Badiane, D. M.; Glazman, L. I. (Phys. Rev. Lett., 2013)

(untitled) - Lee, S.-P.; Michaeli, K.; Alicea, J.; Yacoby, A. (Phys. Rev. Lett., 2014)

(untitled) - Ren, H.; Hart, S.; Wagner, T.; Leubner, P.; Mühlbauer, M.; Brüne, C.; Buhmann, H.; Molenkamp, L. W.; Yacoby, A. (Nat. Phys., 2014)

(untitled) - Pribiag, V. S.; Beukman, A. J. A.; Qu, F.; Cassidy, M. C.; Charpentier, C.; Wegscheider, W.; Kouwenhoven, L. P. (Nat. Nanotechnol., 2015)

(untitled) - Pang, Y.; Shen, J.; Wang, J.; Feng, J.; Qu, F.; Lyu, Z.; Fan, J.; Liu, G.; Ji, Z.; Jing, X.; Yang, C.; Sun, Q.; et al. (arXiv, 2015)

(untitled) - Wiedenmann, J.; Bocquillon, E.; Deacon, R. S.; Hartinger, S.; Herrmann, O.; Klapwijk, T. M.; Maier, L.; Ames, C.; Brüne, C.; Gould, C.; Oiwa, A.; Ishibashi, K.; et al. (Nat. Commun., 2016)

(untitled) - Bocquillon, E.; Deacon, R. S.; Wiedenmann, J.; Leubner, P.; Klapwijk, T. M.; Brüne, C.; Ishibashi, K.; Buhmann, H.; Molenkamp, L. W. (Nat. Nanotechnol., 2017)

(untitled) - Deacon, R. S.; Wiedenmann, J.; Bocquillon, E.; Domínguez, F.; Klapwijk, T. M.; Leubner, P.; Brüne, C.; Hankiewicz, E. M.; Tarucha, S.; Ishibashi, K.; Buhmann, H.; Molenkamp, L. W. (Phys. Rev. X, 2017)

(untitled) - Picó-Cortés, J.; Domínguez, F.; Platero, G. (Phys. Rev. B, 2017)

(untitled) - Peltonen, J. T.; Astafiev, O. V.; Korneeva, Yu. P.; Voronov, B. M.; Korneev, A. A.; Charaev, I. M.; Semenov, A. V.; Golt’sman, G. N.; Ioffe, L. B.; Klapwijk, T. M.; Tsai, J. S. (Phys. Rev. B, 2013)

(untitled) - Sau, J. D.; Setiawan, F. (Phys. Rev. B, 2017)

(untitled) - Prada, E.; San-Jose, P.; Aguado, R. (Phys. Rev. B, 2012)

(untitled) - Rainis, D.; Trifunovic, L.; Klinovaja, J.; Loss, D. (Phys. Rev. B, 2013)

(untitled) - Wang, P.; Liu, J.; Sun, Q.-f.; Xie, X. C. (Phys. Rev. B, 2015)

(untitled) - Liu, J.; Zhang, F.-C.; Law, K. T. (Phys. Rev. B, 2013)

(untitled) - Nilsson, J.; Akhmerov, A. R.; Beenakker, C. W. J. (Phys. Rev. Lett., 2008)